31.1k views
3 votes
Find dy/dx by implicit differentiation: x^2y^3-7xy^2=10

1 Answer

3 votes


x^2y^3-7xy^2=10

Differentiate both sides wrt
x:


(\mathrm d(x^2y^3-7xy^2))/(\mathrm dx)=(\mathrm d(10))/(\mathrm dx)


(\mathrm d(x^2y^3))/(\mathrm dx)-7(\mathrm d(xy^2))/(\mathrm dx)=0

By the product rule,


\left(y^3(\mathrm d(x^2))/(\mathrm dx)+x^2(\mathrm d(y^3))/(\mathrm dx)\right)-7\left(y^2(\mathrm d(x))/(\mathrm dx)+x(\mathrm d(y^2))/(\mathrm dx)\right)=0

By the power and chain rules,


\left(y^3(2x)+x^2\left(3y^2(\mathrm dy)/(\mathrm dx)\right)\right)-7\left(y^2+x\left(2y(\mathrm dy)/(\mathrm dx)\right)\right)=0


\left(2xy^3+3x^2y^2(\mathrm dy)/(\mathrm dx)\right)-7\left(y^2+2xy(\mathrm dy)/(\mathrm dx)\right)=0


(3x^2y^2-14xy)(\mathrm dy)/(\mathrm dx)=7y^2-2xy^3


\implies(\mathrm dy)/(\mathrm dx)=(7y^2-2xy^3)/(3x^2y^2-14xy)

and if
y\\eq0,


\implies\boxed{(\mathrm dy)/(\mathrm dx)=(7y-2xy^2)/(3x^2y-14x)}

User Linse
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.